Electrical Characteristics of Metal Contacts to Carbon Nanowalls. (1st June 2022) - Sun, Zewen; Cho, Minsu; Huang, Lei; Hijiya, Ryota; Kato, Yoshimine; Teii, Kungen
Abstract : The electrical characteristics of metal contacts to vertically-aligned nanographite structures, the so-called carbon nanowalls (CNWs), are examined using nickel as the electrode material. The total resistance between a pair of electrodes on CNWs is regarded as the sum of the serial resistance of CNWs and two metal-CNWs contacts to measure the contact resistance and specific contact resistivity by the transmission line method and transfer line method, respectively. The contact resistance and resistivity are around 2.8 Ω and 0.1 Ω cm 2, respectively, at room temperature and decrease gently to 2.4 Ω and 0.06 Ω cm 2, respectively, when the temperature is increased up to 300 °C. The apparent activation energy corresponding to the conduction barrier at the contact is in the range of 10 −3 eV to 10 −2 eV, which is comparable with that for the sheet resistance of CNWs. The contact resistance occupies a large portion of the total resistance between a pair of electrodes even at high temperatures, thus affecting electrical signal measurement in electronic and electrochemical device applications.